Pregnancy-Associated Plasma Protein-A as an Inflammatory Biomarker in Patients Undergoing Coronary Artery Bypass Surgery - Onk, Oruc Alper; Onk, Didem; Ozcelik, Fatih; Gunay, Murat (Progress in Nutrition, 2022)
Study Objectives: Data is limited to show whether PAPA-A and/or VEGF are useful tests to predict the prognosis of coronary artery disease. We sought to investigate the potential roles of PAPP-A and VEGF in predicting the severity of coronary artery disease in patients undergoing coronary artery bypass grafting. Methods: A total of 212 male patients who were scheduled to undergo coronary angiography were included. Patients were divided into five groups. Group 0: Patients with normal coronary arteries, Group 1: Patients with <50% stenosis in only one coronary artery, Group 2: Patients with >50% stenosis in 1 or 2 coronary arteries, Group 3: Patients with >50% stenosis in 3 or 4 coronary arteries, Group 4: Patients with >50% stenosis in 5 or more coronary arteries. PAPP-A, TNF-α, IL-6, and VEGF, blood samples were centrifuged at a rate of 3500 rpm for 10 minutes. Results: In the preoperative measurements, all inflammatory biomarkers except VEGF were significantly associated with an increasing number of diseased coronary arteries where hsCRP and PAPP-A showed the highest level of association. In the 7th postoperative day measurements, only PAPP-A and IL-6 showed significant association with the dependent outcome. PAPP-A was found to be associated with an increased risk of a higher number of diseased coronary arteries. Conclusion: PAPP-A offers a useful tool in the diagnosis of the severity of coronary artery involvement in patients undergoing CABG. Its use alone or in combination with TNF- α and/or CRP may potentially distinguish patients with and without advanced disease.